1994
DOI: 10.1002/cyto.990150107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field pulses on the viability and on the membrane‐bound immunoglobulins of LPS‐activated murine B‐lymphocytes: Correlation with the cell cycle

Abstract: The effects of microsecond electropulses (1-5 kV/cm) on the viability of murine B lymphocytes and on their binding of antibodies by surface immunoglobulin (Ig) were studied in relation to the cell cycle. Before electropulsing, cultures given 48 h mitogenic stimulation showed at least two cell subpopulations, which were distinguishable by their levels of surface-Ig expression as assessed with FITC-labelled antibodies against mouse Ig. The immunofluorescence intensity of cells in S and G2/M phases was higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The 570 nm absorbance of the samples (including light scattering) was maintained at about 0.1. The time course of red fluorescence was followed continuously (resolution 0.1 s) from 1 min before to [10][11][12][13][14][15] min after field application (recording mode of the spectrophotometer).…”
Section: Electropermeabilization Of the Plasma Membranementioning
confidence: 99%
See 3 more Smart Citations
“…The 570 nm absorbance of the samples (including light scattering) was maintained at about 0.1. The time course of red fluorescence was followed continuously (resolution 0.1 s) from 1 min before to [10][11][12][13][14][15] min after field application (recording mode of the spectrophotometer).…”
Section: Electropermeabilization Of the Plasma Membranementioning
confidence: 99%
“…Simultaneous measurement of PI and CF fluorescence emitted by control or electromanipulated cells was performed in a Fluvo-Metricell flow cytometer (HEKA elektronik, Lambrecht, Federal Republic of Germany; for details, see 14). The red channel of the cytometer was calibrated for intracellular PI content.…”
Section: Calibration Of the Flow Cytometermentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, it is important to determine whether such field exposure induces undesirable effects on the cells, and if so, to identify conditions that avoid or minimize these negative effects. Extensive studies have been reported for cell field exposure to pulse and DC electrical fields applicable to electroporation and cell fusion [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These studies have shown that field exposure can alter cell membrane potential and membrane structure [28,[31][32][33], cause cells to deform [28,30,[32][33][34], increase cell membrane permeability [32][33][34]39], lead to reversible and irreversible dielectric breakdown of the cell membrane [26,27,39], and cause cellular DNA damage [36].…”
Section: Introductionmentioning
confidence: 99%